Childhood Trauma, Emotion Regulation, and Pain in Individuals With Alcohol Use Disorder - Zaorska, Justyna; Kopera, Maciej; Trucco, Elisa M.; Suszek, Hubert; Kobyliński, Paweł; Jakubczyk, Andrzej (Frontiers in Psychiatry, 2020)
Introduction: Several studies have confirmed that the experience of childhood trauma, poor emotion regulation, as well as the experience of physical pain may contribute to the development and poor treatment outcomes of alcohol use disorder (AUD). However, little is known about how the joint impact of these experiences may contribute to AUD. Objectives: To analyze associations between childhood trauma, emotion regulation and pain in individuals with AUD. Methods: The study sample included 165 individuals diagnosed with AUD. The Childhood Trauma Questionnaire was used to investigate different types of trauma during childhood (physical, emotional and sexual abuse and neglect), the Brief Symptom Inventory was used to assess anxiety symptoms, the Difficulties in Emotion Regulation Scale (DERS) was used to assess emotional dysregulation, and the Pain Resilience Scale as well as Pain Sensitivity Questionnaire were used to measure self-reported pain tolerance and sensitivity. Results: Childhood emotional abuse (CTQ subscale score) was positively associated with anxiety, anxiety was positively associated with emotional dysregulation, and emotional dysregulation was negatively associated with pain tolerance. Accordingly, there was support for a significant indirect negative association between childhood emotional abuse and pain tolerance. The serial mediation statistical procedure demonstrated that anxiety and emotional dysregulation mediated the effect of childhood emotional abuse on pain resilience among individuals with AUD. Conclusions: Targeting emotional dysregulation and physical pain that may result from childhood trauma may have particular therapeutic utility among individuals treated for AUD.